2013
DOI: 10.1152/jn.00460.2012
|View full text |Cite
|
Sign up to set email alerts
|

Rapid regulation of tonic GABA currents in cultured rat hippocampal neurons

Abstract: Subacute and chronic changes in tonic GABAergic inhibition occur in human and experimental epilepsy. Less is known about how tonic inhibition is modulated over shorter time frames (seconds). We measured endogenous tonic GABA currents from cultured rat hippocampal neurons to evaluate how they are affected by 1) transient increases in extracellular GABA concentration ([GABA]), 2) transient postsynaptic depolarization, and 3) depolarization of presynaptic cells. Transient increases in [GABA] (1 μM) reduced tonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…However, the work carried out in Richerson's laboratory has shown that the reverse potential of GAT1 under physiologically relevant conditions is near the resting potential of neurons and that GAT1 reversal can occur relatively easily (Wu et al, 2001(Wu et al, , 2007. The authors conclude that GAT1-mediated GABA release can contribute to phasic inhibition and that GAT1 can finely regulate tonic inhibition (Wu et al, 2007;Ransom et al, 2013). Because the carrier-mediated component of the evoked release here observed is triggered by low micromolar GABA, it might have physiological significance.…”
Section: Discussionmentioning
confidence: 70%
“…However, the work carried out in Richerson's laboratory has shown that the reverse potential of GAT1 under physiologically relevant conditions is near the resting potential of neurons and that GAT1 reversal can occur relatively easily (Wu et al, 2001(Wu et al, , 2007. The authors conclude that GAT1-mediated GABA release can contribute to phasic inhibition and that GAT1 can finely regulate tonic inhibition (Wu et al, 2007;Ransom et al, 2013). Because the carrier-mediated component of the evoked release here observed is triggered by low micromolar GABA, it might have physiological significance.…”
Section: Discussionmentioning
confidence: 70%
“…Yet, due to its operation as a passive transporter, GAT-1 can invert the direction of GABA transport, even on short time scales, depending on the membrane potential and the cross-membrane concentration gradients of GABA and the co-transported Na + and Cl - ions (Wu et al, 2007; Ransom et al, 2013). Likewise, based on work in acute cortical slices, the hypothesis has been put forward that GAT-2/3 may preferentially operate in reverse mode and furnish GABA to interneurons, thus constraining their activity (Kinney, 2005; Kirmse and Kirischuk, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, during synchronous and repetitive activation of numerous GABAergic synapses via electrical stimulation, impairment of GATs was found to induce a massive spillover of transmitter and synaptic crosstalk (Thompson and Gähwiler, 1992; Jackson et al, 1999; Overstreet and Westbrook, 2003; Keros and Hablitz, 2005; Gonzalez-Burgos et al, 2009). In conditions between such extremes, GATs may subserve a dual role, quickly switching between removing an excess of ambient GABA and contributing to slow phasic inhibition (Gaspary et al, 1998; Wu et al, 2007; Ransom et al, 2013). As it is unclear which direction of transport prevails in various phases of recurrent AP activity, it is difficult to predict the net effects of GAT impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in GABA A R number is likely to occur through the rapid lateral transit and clustering leading to enhanced responses (Kittler and Moss, 2003; Semyanov et al, 2004; Bannai et al, 2009; Pavlov et al, 2009; Ransom et al, 2010; Luscher et al, 2011; Brickley and Mody, 2012; Ransom et al, 2013; Dominguez et al, 2014, 2015). Interestingly, the dynamic lateral mobility of GABA A Rs can be enhanced by neuronal hyperactivity and operate in the 10s-of-milliseconds time range (Bannai et al, 2009; Dominguez et al, 2015), thus providing an exceptionally rapid negative feedback through the control of GABA A R number (Gaiarsa et al, 2002; Petrini et al, 2004; Luscher et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CA1 PC synapses do not hold δ-GABA A Rs and α1/4/6β and α5- receptors are scarce at those synapses. However, lateral diffusion of extrasynaptic receptors can increase the number of α1/4/6β and α5- receptors at synapses (Semyanov et al, 2004; Bannai et al, 2009; Pavlov et al, 2009; Ransom et al, 2010, 2013; Brickley and Mody, 2012). α5- receptors show slow desensitization and outward rectification and high GABA affinity contributing to the tonic GABA current (Caraiscos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%